Análise térmica das células de um módulo fotovoltaico utilizando redes de Bragg em fibra óptica para um sistema de bombeamento de água - Dalla Corte, Vinícius (2022)
The present study aims at presenting the use of fiber optic sensors, based in Bragg gratings for monitoring and analyzing the thermal behavior of the cells of a photovoltaic module, used to verify the temperature of some cells during the beginning and the end of the process operation of a water pumping system. The system was implemented at Federal University of Technology - Paraná – UTFPR – campus of Pato Branco. Sixteen Fiber Bragg Gratings (FBGs) were used, placed at the front surface of the module, allowing the temperature monitoring of sixteen cells during the operation of the water pumping system. The photovoltaic cells which compose a module are key factors for power generation as well as for the good functioning of the same, resulting in a prolonged lifespan if connected to a water pumping system, for instance. The monitoring of photovoltaic water pumping systems currently presents limitations, such as dirt, cracks and fissures or hot spots, in relation to the monitoring of the cells temperature over time. The use of FBGs sensors intends to assist in studies and research aimed at monitoring the cells temperature of a photovoltaic panel, through the use of clean and renewable energy, that is to say, the photovoltaic. Due to the fact that FGB sensors are inscribed on a single-mode fiber segment, they have reduced size and weight, resulting in no shading over the module, what enables the study of thermal variations impact caused by environmental and electrical factors on the water pumping system and thereby the verification of its performance and possible usage potentialities, such as the study of the beginning and the end of the water pumping operation. The system is composed of sixteen FGB sensors, with the water pump directly connected to the photovoltaic module.